Materialização de uma atmosfera: um lugar entre o céu e a terra - Maria Benedita Almeida Campos Coelho e Santos (2015)
The act of projecting architecture is based on the man's need to organize the space that surrounds him, taking over it through the body of senses and creating memories of places wich contribute to our way of seeing and being in the world. By linking the man to the architecture and the perception of spaces created by it, we are lead to reflect and connect some concepts such as place, senses, memories, identity, emotions and atmospheres. We are interested in analysing and understanding the concept of architectural atmosphere and the role of the architect in its projection, by creating spaces that transcend the most physical and material level of architecture, entering an immaterial and intangible domain. To this end, it is elected a significant place in the individual space experience where is pretended the materialization of the consolidated ideas, by proposing a project of a chapel in the landscape. It is the realization of a place for the body of senses that transcends its objective meaning. The option of choosing a religious program is due to their highly sensitive and emotional nature which results in multisensorial experiences, the materialization of an atmosphere.